The HIDDEN Protocol: An Australian Prospective Cohort Study to Determine the Utility of Whole Genome Sequencing in Kidney Failure of Unknown Aetiology - Soraru, Jacqueline; Jahan, Sadia; Quinlan, Catherine; Simons, Cas; Wardrop, Louise; O’Shea, Rosie; Wood, Alasdair; Mallawaarachchi, Amali; Patel, Chirag; Stark, Zornitza; Mallett, Andrew John (Frontiers in Medicine, 2022)
Early identification of genetic kidney disease allows personalised management, clarification of risk for relatives and guidance for family planning. Genetic disease is underdiagnosed, and recognition of genetic disease is particularly challenging in patients with kidney failure without distinguishing diagnostic features. To address this challenge, the primary aim of this study is to determine the proportion of genetic diagnoses amongst patients with kidney failure of unknown aetiology, using whole genome sequencing (WGS). A cohort of up to 100 Australian patients with kidney failure of unknown aetiology, with onset <50 years old and approved by a panel of study investigators will be recruited via 18 centres nationally. Clinically accredited WGS will be undertaken with analysis targeted to a priority list of ~388 genes associated with genetic kidney disease. The primary outcome will be the proportion of patients who receive a molecular diagnosis (diagnostic rate) via WGScompared with usual -care (no further diagnostic investigation). Participant surveys will be undertaken at consent, after test result return and one year subsequently. Where there is no or an uncertain diagnosis, future research genomics will be considered to identify candidate genes and new pathogenic variants in known genes. All results will be relayed to participants via the recruiting clinician and/or kidney genetics clinic. The study is ethically approved (HREC/16/MH/251) with local site governance approvals in place. The future results of this study will be disseminated and inform practical understanding of the potential monogenic contribution to kidney failure of unknown aetiology. These findings are anticipated to impact clinical practice and healthcare policy. Study Registration: HREC/16/MH/251 – AGHA study registration number through DoRA Queensland Health (https://dora.health.qld.gov.au/qldresearchjspui/cris/project/pj08509)